ANALISIS KEMAMPUAN BERPIKIR KRITIS MATEMATIS - Siregar, Yulia Pratiwi (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2024)
This research aims to describe students' critical thinking abilities. Critical thinking skills are very necessary in accordance with educational goals and in improving the quality of human resources (HR). This type of research is descriptive research with the data analysis used is a literature review. A review was carried out on 10 journals that studied students' critical thinking abilities. Based on the analysis carried out, it was concluded that critical thinking skills must be possessed by every student. This ability can occur with collaboration between students and teachers, where a teacher must have expertise in creating dynamic problems so that students can be stimulated to solve the problems given and create very creative ideas. This critical thinking ability can certainly be the basis for creating human resources who are critical and creative and have high competitiveness.